2008
DOI: 10.1111/j.1365-2702.2008.02348.x
|View full text |Cite
|
Sign up to set email alerts
|

Education for patients with chronic kidney disease in Taiwan: a prospective repeated measures study

Abstract: A predialysis educational program with disease-specific knowledge and information is feasible and may provide positive outcomes for patients. Topics on the uses of Chinese herbs should be included for people who are likely to use alternative therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 27 publications
1
43
0
Order By: Relevance
“…Studies in hypertension reveal patients who do not attend educational sessions are more likely to be older, 35 although when older patients do participate, benefits in both knowledge and health measures are observed. 36 Therefore, although there were age differences between responders and nonresponders, it is not clear how this may have affected our results.…”
Section: Discussionmentioning
confidence: 84%
“…Studies in hypertension reveal patients who do not attend educational sessions are more likely to be older, 35 although when older patients do participate, benefits in both knowledge and health measures are observed. 36 Therefore, although there were age differences between responders and nonresponders, it is not clear how this may have affected our results.…”
Section: Discussionmentioning
confidence: 84%
“…; Choi & Lee ) showed large effect sizes (d = 1.61–1.27) for between‐group differences at follow‐up for knowledge, although Yen et al . 's () within‐group analysis found CKD knowledge was higher at 6 months than at baseline, but below baseline at 12 months.…”
Section: Resultsmentioning
confidence: 98%
“…Two studies (Yen et al . ; Chen et al . ) developed their own questionnaires to assess this outcome, and although neither study reported specific items, both questionnaires assessed knowledge of kidney function and dietary restrictions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is unknown whether knowledge improved during the first few weeks or months or only at the end of the study. Teng et al (2013) assessed knowledge at five time points-baseline, 3, 6, 9 and 12 months-using the Renal Protection Knowledge (RPK) checklist, which measures participants' knowledge of renal function protection, knowledge of using Chinese herbs related to renal function, and CKD diet (Yen, Huang, & Teng, 2008). However, the checklist is not available in English.…”
Section: Knowledgementioning
confidence: 99%